Inhibitory effects of idoxifene on hepatic fibrosis in rats - Zhou Ya-jun; Yin Dong-mei; Chen Hong-shan; Shi Jian-hua; Sha Bao-xi; Wang Xing (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of a tissue-specific selective estrogen receptor modulator, idoxifene, on hepatic fibrosis in rats. Methods: Hepatic fibrosis was induced by dimethylnitrosamine (DMN) in male rats. The DMN model of hepatic fibrosis and the hepatocytes undergoing oxidative stress were treated with idoxifene respectively. The effect of idoxifene on hepatic fibrosis in the DMN model was examined by immunohistochemistry. Effects of idoxifene on antioxidant enzyme levels of copper, zinc-dependent superoxide dismutase (CuZn-SOD), and cellular glutathione peroxidase (GSHPx) were measured by ELISA. Effects of idoxifene on activation, proliferation, and apoptosis of culture-activated hepatic stellate cells (HSC) were analysed by immunohistochemistry, bromodeoxyuridine (BrdU) uptake, and flow cytometry, respectively. Results: Idoxifene could markedly suppress DMN-induced hepatic fibrosis in male rats. A treatment of 0.4mgdotkg-1dotd-1 of idoxifene reduced the protein levels of collagen in the DMN model by 41.19% (P